2019
DOI: 10.1007/s00531-019-01677-y
|View full text |Cite
|
Sign up to set email alerts
|

Gneiss-forming events in the Saglek Block, Labrador; a reappraisal of the Uivak gneiss

Abstract: The Archean gneiss complex of the Saglek Block of Labrador is a part of the North Atlantic Craton, and is correlated with southern West Greenland, both being metamorphosed during a ca. 2.7 Ga event. The main component of the complex is the Eoarchean Uivak orthogneiss, which includes lenses of the Nulliak supracrustal assemblage. Both lithologies are cut by the mafic Saglek metadykes. The Uivak gneisses have been divided into Uivak I grey gneiss and Uivak II augen gneiss. The former underwent ca. 3.6 Ga high-T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…A section of the Saglek Block investigated in recent studies by the same group (Kusiak et al 2018;Sałacinśka et al 2018Sałacinśka et al , 2019Whitehouse et al 2019) extends for 80 km along the Labrador coast, from Ramah Bay in the north to Hebron Fjord in the south (Fig. 1b).…”
Section: Geological Settingmentioning
confidence: 95%
See 3 more Smart Citations
“…A section of the Saglek Block investigated in recent studies by the same group (Kusiak et al 2018;Sałacinśka et al 2018Sałacinśka et al , 2019Whitehouse et al 2019) extends for 80 km along the Labrador coast, from Ramah Bay in the north to Hebron Fjord in the south (Fig. 1b).…”
Section: Geological Settingmentioning
confidence: 95%
“…1b). Gneisses in the southern part of the section formed in several stages throughout the Archean, with the oldest and most abundant TTG-type protoliths (the Uivak gneiss) formed between c. 3850 and 3600 Ma (Schiøtte et al 1989;Komiya et al 2017;Kusiak et al 2018;Sałacinśka et al 2018Sałacinśka et al , 2019, with lesser episodes of felsic plutonism at c. 3.3-3.0, 2.7 and 2.5 Ga (Schiøtte et al 1990(Schiøtte et al , 1992Krogh & Kamo 2006;Komiya et al 2015;Sałacinśka et al 2019). Krogh & Kamo (2006) suggested that TTG gneisses from outcrops around Saglek Bay differ in age across the Handy Fault (Fig.…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, even if there is no clear evidence that the supracrustal rocks were intruded by the Saglek dyke, the supracrustal rocks intruded by the Uivak Gneiss can be identified as the Nulliak supracrustal rocks. The Uivak Gneiss comprises polygenetic orthogneiss with different magmatic ages of their protoliths from 3.9 to 3.6 Ga, and with composition from tonalite to iron-rich monzodiorite (Collerson, 1983;Komiya et al, 2017;Krogh & Kamo, 2006;Kusiak et al, 2018;Regelous & Collerson, 1996;Sałaci nska et al, 2018;Sałaci nska et al, 2019;Schiøtte et al, 1989aSchiøtte et al, , 1989bShimojo et al, 2016;Vezinet et al, 2018;Wanless, Bridgwater, & Collerson, 1979;Wasteneys, Wardle, & Krogh, 1996). Although the presence of the pre-3.9 Ga gneiss in the Saglek Block is still controversial , it is widely accepted that the protoliths of the Uivak Gneiss were formed in the Eoarchean (> 3.6 Ga).…”
Section: Geological Outline Of the Nulliak Supracrustal Rocks In Northern Labrador Canadamentioning
confidence: 99%